The Poverty Impact of Rural Roads : Evidence from Bangladesh - Khandker, Shahidur R.; Bakht, Zaid; Koolwal, Gayatri B. (World Bank, Washington, DC, 2012)
The rationale for public investment in rural roads is that households can better exploit agricultural and nonagricultural opportunities to use labor and capital more efficiently. But significant knowledge gaps remain as to how opportunities provided by roads actually filter back into household outcomes and their distributional consequences. This paper examines the impacts of rural road projects using household-level panel data from Bangladesh. Rural road investments are found to reduce poverty significantly through higher agricultural production, higher wages, lower input and transportation costs, and higher output prices. Rural roads also lead to higher girls' and boys' schooling. Road investments are pro-poor, meaning the gains are proportionately higher for the poor than for the non-poor.